HISTOLOGICAL STUDY OF FIBULAR ANLAGE, THE EMBRYONIC TISSUE REMNANT IN TYPE II HEMIMELIA CASES - Mustafa, Snoor Jalal (European Scientific Journal, ESJ, 2015)
Background: Fibular hemimelia or fibular hypoplasia is the most common congenital longitudinal limb deficiency characterized by complete or partial absence of the fibula bone and it was described initially as a condition that is related to aplasia or hypoplasia of the fibula. Tethering effect of fibular anlage, the primordium of fibula which is frequently found with type II hemimelia may contribute to the deformities in the tibia and ankle. The etiology is unclear; the deformity is probably due to disruptions during the critical period of embryonic limb bud development. Objective: to find out and study the histological nature of the excised fibular anlage. Patient and Method: From 40 limbs belonging to 32 patients (some were bilateral) who underwent surgical operation,19 fibular anlagen were found and excised as a first step of correction of lower limb deformity and bone elongation, the anlagen underwent fixation and tissue processing then the sections examined under light microscope. Results: the histological examination revealed presence of hyaline cartilage, chondrocytes forming isogenous group and a lot of fibrous tissue with no sign of bone formation. Conclusion: persistence of cartilaginous model of the fibular anlage confirms arrested growth of the limb bud and failure of endochondral ossification to commence.